A CASE STUDY OF STUDENTS' ENGLISH LEARNING INTEREST AT MTS. RADEN RAHMAT - Lailatul Mukarromah; Mulis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning interest plays a crucial role in promoting students' engagement and persistence in learning English as a Foreign Language (EFL). However, limited studies have explored how students' English learning interest develops within the context of pesantren-based junior secondary schools. This study aimed to explore students' English learning interest at MTs. Raden Rahmat and to identify the factors influencing through the Four-Phase Model of Interest Development. A qualitative case study design was employed involving forty eighth-grade students, with six students purposively selected for semi-structured interviews. One English teacher also participated as a key informant to provide complementary perspectives. Data were collected through questionnaires, classroom observations, and semi-structured interviews and analysed using thematic analysis, while descriptive statistics were used to summarise the questionnaire results. Data triangulation was employed to enhance the trustworthiness of the findings. The findings revealed that 60% of the students demonstrated triggered situational interest, 25% maintained situational interest, and 15% exhibited emerging individual interest, whereas none reached the well-developed individual interest phase. Findings from the interviews further indicated that students perceived English as a difficult subject, low intrinsic motivation, and limited independent learning opportunities were the major factors hindering the development of their learning interest. Overall, the findings suggest that students' English learning interest remains predominantly at the situational level, influenced by meaningful classroom experiences and their perceptions of the relevance and value of English. Therefore, English teachers should implement interactive, contextual, and student-centred instructional practices to foster more sustainable individual interest in learning English.